2009
DOI: 10.1017/s0047279409003110
|View full text |Cite
|
Sign up to set email alerts
|

What is the Impact of Public Care on Children's Welfare? A Review of Research Findings from England and Wales and their Policy Implications

Abstract: The outcomes for children in public care are generally considered to be poor. This has contributed to a focus on reducing the number of children in care: a goal that is made explicit in the provisions of the current Children and Young Persons Bill. Yet while children in care do less well than most children on a range of measures, such comparisons do not disentangle the extent to which these difficulties pre-dated care and the specific impact of care on child welfare. This article explores the specific impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 22 publications
0
43
0
1
Order By: Relevance
“…Moreover there is a relative lack of evidence of positive child outcomes to support the use of state interventions such as placing a child on a register or in out-of-home care. There is evidence that children in out-of-home care can fare slightly better than children involved with adverse childhoods who stay with birth families (Forrester et al, 2009), but studies usually fail to control for the economic circumstances of the birth and care families, including the payments and other resources available to foster carers or residential care providers but not to birth families. Compared with the general population, both groups of children fare much worse (Vinnerljung et al, 2006).…”
Section: Why An Inequities Approach?mentioning
confidence: 99%
“…Moreover there is a relative lack of evidence of positive child outcomes to support the use of state interventions such as placing a child on a register or in out-of-home care. There is evidence that children in out-of-home care can fare slightly better than children involved with adverse childhoods who stay with birth families (Forrester et al, 2009), but studies usually fail to control for the economic circumstances of the birth and care families, including the payments and other resources available to foster carers or residential care providers but not to birth families. Compared with the general population, both groups of children fare much worse (Vinnerljung et al, 2006).…”
Section: Why An Inequities Approach?mentioning
confidence: 99%
“…Garrett's (2008) early critique of SWPs rested on two key points: first he argued that the characterisation of the looked after system as a 'failing system' is primarily ideological and does not take account of the complexity of experience that the care system encompasses. In this, he drew on the arguments of researchers such as Stein (2006) and Forrester et al (2009) who have emphasised the heterogeneity of children's experiences in the looked after system and who maintain that outcomes for looked after children reflect the needs that bring them into care. Second, Garrett claimed that SWPs were introduced without meaningful consultation of looked after children or their parents Other critics have suggested that SWPs will be required to meet the same bureaucratic demands as local authority children's services, particularly in relation to the much criticised electronic records system, the Integrated Children's System (Cardy, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to emotional and behavioural difficulties, Option 2 children showed no particular differences compared with control group children. This may, in part, be because entering care was one of the most powerful ways to reduce behavioural problems (see Forrester et al 2009). Option 2 was therefore achieving a comparable level of success at avoiding behavioural problems compared with an alternative that included providing permanent alternative care for 38% of children.…”
Section: Implications Of the Findingsmentioning
confidence: 99%